2015
DOI: 10.1139/cjpp-2014-0356
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of renal hyporesponsiveness to BNP in heart failure

Abstract: The B-type natriuretic peptide (BNP), a member of the family of vasoactive peptides, is a potent natriuretic, diuretic, and vasodilatory peptide that contributes to blood pressure and volume homeostasis. These attributes make BNP an ideal drug that could aid in diuresing a fluid-overloaded patient who had poor or worsening renal function. Despite the potential benefits of BNP, accumulating evidence suggests that simply increasing the amount of circulating BNP does not necessarily increase natriuresis in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Various mechanisms have been proposed to account for the diminished effectiveness of the NPS in the setting of CHF ( Table ) …”
Section: Potential Mechanisms Of Reduced Effectiveness Of the Natriurmentioning
confidence: 99%
“…Various mechanisms have been proposed to account for the diminished effectiveness of the NPS in the setting of CHF ( Table ) …”
Section: Potential Mechanisms Of Reduced Effectiveness Of the Natriurmentioning
confidence: 99%
“…Since NPR‐C signalling may be up‐regulated in HF and may act in a manner similar to β ‐blockers actions, pharmacological agents that also target this specific signalling pathway may be beneficial. This affirmation is supported by the evidence that NPR‐C signalling may be important not only in improving coronary perfusion but also its activation may prevent against ischemia/reperfusion injury . Interestingly, the authors found that the vasorelaxant effect of NPR‐C signalling was increased in the presence of nitric oxide (NO) synthase inhibition, suggesting that they may be synergistic and complementary cardioprotective roles for NPR‐C signalling and NO‐mediated signalling in the coronary vasculature.…”
Section: Clinical Effectiveness Of Activating Specific Natriuretic Pementioning
confidence: 84%
“…The inhibition of one pathway may thus be compensated for by the upregulation of the other. This may be of particular clinical significance in patients with HF who are known to have endothelial dysfunction and thus reduced or loss of NO pathway …”
Section: Clinical Effectiveness Of Activating Specific Natriuretic Pementioning
confidence: 99%
See 2 more Smart Citations